Inherent optical properties of dissolved and particulate matter in an Arctic fjord (Storfjorden, Svalbard) in early summer - Petit, Tristan; Hamre, Børge; Sandven, Håkon; Röttgers, Rüdiger; Kowalczuk, Piotr; Zablocka, Monika; Granskog, Mats A. (Ocean Science, 2022)
There have been considerable efforts to understand the hydrography of Storfjorden (Svalbard). A recurring winter polynya with large sea ice production makes it an important region of dense water formation at the scale of the Arctic Ocean. In addition, this fjord is seasonally influenced by freshwater inputs from sea ice melt and the surrounding islands of the Svalbard archipelago, which impacts the hydrography. However, the understanding of factors controlling the optical properties of the waters in Storfjorden are lacking and are crucial for the development of more accurate regional bio-optical models. Here, we present results from the first detailed optical field survey of Storfjorden conducted in early summer of 2020. Our observations are based on spectrometric analysis of water samples and in situ vertical profiles with an absorption and attenuation meter, a fluorometer, and a conductivity, temperature, and depth (CTD) sensor. In addition to the expected seasonal contribution from phytoplankton, we find that in early summer waters in Storfjorden are optically complex with a significant contribution from coloured dissolved organic matter (CDOM, 33 %–64 % of the non-water absorption at 443 nm) despite relatively low CDOM concentrations and in the nearshore or near the seabed from non-algal particles (up to 61 % of the non-water absorption at 550 nm). In surface waters, the spatial variability of light attenuation was mainly controlled by inorganic suspended matter originating from river runoff. A distinct subsurface maximum of light attenuation was largely driven by a subsurface phytoplankton bloom, controlled by stratification resulting from sea ice melt. Lastly, the cold dense bottom waters of Storfjorden from winter sea ice production periodically overflows the sill at the mouth of the fjord and can thus reach the Fram Strait. It contained elevated levels of both non-algal particles and dissolved organic matter, which are likely caused by the dense flows of the nepheloid layer interacting with the sea bed.